Primary Central Nervous System Lymphoma – Management and Outcome in the 'haematology era'. (12th October 2019) - Kumar, Siddhant; Islim, Abdurrahman; Ali, Tamara; Smith, Jeffery; Haylock, Brian; Shenoy, Aditya; Husband, David; J Mills, Samantha; Brodbelt, Andrew; Chavredakis, Emmanuel; Lawson, David; Chapman, Grace; et al.
Abstract: Introduction: Primary CNS lymphoma (PCNSL) requires a biopsy for diagnosis but can be inconclusive when steroids are administered. Without treatment median survival is 1.5–3.3 months, improving to 10–20 months with oncological treatment. This study aimed to compare outcomes of PCNSL treated under haematology to those of clinical oncologists. Methods: Retrospective casenote review of patients with PCNSL treated under oncologists (2006–2010) and haematologists (2011–2016). Results: 121 cases were identified (median age 63 years; range 19–84). Median WHO performance status (PS) was 1. 11.6% required repeat biopsy. 10 patients were managed palliatively due to poor PS. 67 cases were managed under haematology. Median symptom duration was 28 days (range 2–540). Median time from MRI to diagnosis was 18 days (range 6–232). 66 patients received chemotherapy, 1 received radiotherapy. Median overall survival (OS) was 8 months (95%CI: 0.7–15.3), 5-year OS was 22.4%. 44 cases were managed under oncology. Median symptom duration was 28 days (range 2–365). Median time from MRI to diagnosis was 16 days (range 6–309). 34 patients received radiotherapy first-line, 10 received chemotherapy. Median OS was 7 months (95%CI: 0–21.5), 5-year OS was 15.9%. Multivariate analysis demonstrated PS (HR 2.02 (95%CI: 1.08–3.76)) and symptom duration (HR 0.63 (95%CI: 0.41–0.96)) to be significant prognostic indicators for OS. Discussion: PCNSL carries poor prognosis and outcomes from the 'haematology era' are similar to those achieved by clinical oncologists. Delay in diagnosis leads to worse outcomes and highlights the ongoing need to streamline current clinical services to improve outcomes.